Self-Esteem and Life Satisfaction Among Adolescents in Semarang: Communication with Peers as a Mediator - Kusuma, Arneta Nadila; Widyorini, Endang (Psikoborneo: Jurnal Ilmiah Psikologi, 2025)
The decline in life satisfaction during adolescence is a significant concern due to its negative effects on psychological well-being and development. Factors contributing to life satisfaction include self-esteem and communication with peers. This study aimed to examine the relationship between self-esteem and life satisfaction among adolescents in Semarang, with communication with peers as a mediating variable. The proposed hypothesis was that communication with peers mediates the relationship between self-esteem and life satisfaction. The population of this study includes students who are actively attending junior high schools in Semarang. A quantitative approach with a simple mediation design was used. Data were collected from 296 participants using three instruments: the Rosenberg Self-Esteem Scale, the Satisfaction with Life Scale–Children (SWLS-C), and the Adolescent Peer Communication Scale. Data were analyzed using Structural Equation Modeling (SEM). The results showed a positive and significant relationship between self-esteem and life satisfaction, mediated by communication with peers (coefficient = 0.019; 95% CI [0.008–0.029]). These findings highlight the important role of peer communication in mediating the relationship between self-esteem and life satisfaction in adolescents. This underscores the importance of developing peer communication skills as a strategy to enhance adolescents’ life satisfaction.Penurunan life satisfaction selama masa remaja merupakan masalah penting yang dapat berdampak negatif pada kesejahteraan psikologis dan perkembangan remaja. Beberapa faktor yang berkontribusi terhadap life satisfaction adalah self-esteem dan communication with peers. Penelitian ini bertujuan untuk mengetahui hubungan antara self-esteem dan life satisfaction pada remaja di Kota Semarang yang dimediasi oleh communication with peers. Adapun hipotesis dalam penelitian ini adalah terdapat hubungan antara self-esteem dan life satisfaction pada remaja di Semarang yang dimediasi oleh communication with peers. Populasi penelitian meliputi siswa yang aktif bersekolah di tingkat Sekolah Menengah Pertama di Kota Semarang. Pendekatan kuantitatif dengan desain mediasi sederhana digunakan dalam penelitian ini. Data dikumpulkan dari 296 partisipan menggunakan tiga instrumen, yaitu Rosenberg Self-Esteem Scale, Satisfaction with Life Scale–Children (SWLS-C), dan skala Adolescent Peer Communication. Analisis data dilakukan dengan metode Structural Equation Modelling (SEM). Hasil menunjukkan bahwa terdapat hubungan positif dan signifikan antara self-esteem dan life satisfaction yang dimediasi oleh communication with peers (koefisien = 0,019; 95% CI [0,008–0,029]). Hasil penelitian ini menegaskan peran penting communication with peers dalam memediasi hubungan antara self-esteem dan life satisfaction remaja. Temuan ini menggarisbawahi pentingnya pengembangan keterampilan komunikasi antar teman sebaya sebagai strategi untuk meningkatkan kepuasan hidup remaja.